State, Power and Community in Early Modern Russia - Davies, B. author. aut Link
X, 308 p.
Keywords: State, Power and Community in Early Modern Russia is a vivid reconstruction of life in one of the garrison towns built on Muscovy's southern steppe frontier in the early Seventeenth-century to defend against Tatar raids. It focuses on how the colonization process shaped power relations in a particular southern garrison community, both at the village level, within the land commune, and at the district level, between the general garrison community and the appointed officials representing state authority.